Spatial distribution of harmful trace elements in Chinese coalfields: An application of WebGIS technology - Cao, Qingyi; Yang, Liu; Ren, Wenying; Song, Yuling; Huang, Siyan; Wang, Yuetian; Wang, Zhiying (The Science of the total environment, 2021)
Harmful trace elements in coal have caused serious damage to the environment and human health. Understanding their spatial distribution is helpful for environmental health assessment and for their effective control and utilization. To further explore the geospatial distribution of harmful trace elements found in Chinese coals, this work constructed the Trace Elements in Chinese Coals Database Management System (TECC), and analysed the spatial distribution of harmful trace elements by applying spatial data algorithms and visual technology of WebGIS. The main results are as follows: (1) The mean concentrations of 25 harmful trace elements (Ag, As, B, Ba, Be, Cd, Cl, Co, Cr, Cu, F, Hg, Mn, Mo, Ni, P, Pb, Sb, Se, Sn, Th, Tl, U, V, Zn) in Chinese coals are provided, using the “reserve-concentration” weighted calculation method; (2) Using As, Hg, F, and U as examples, the spatial distribution of harmful trace elements in Chinese coalfields is visually displayed; (3) Harmful trace elements are extremely unevenly distributed in Chinese coalfields; they are mainly concentrated in south China, especially in the southwest region, and some elements may also be concentrated in coals from northwest, northeast, and north China. The enrichment of harmful trace elements in Chinese coals is the result of a combination of multiple factors, such as the nature of the region the coal is sourced from, sedimentary facies, coal-forming plants, and magmatic hydrothermal processes. This work can serve as a reference for the study of harmful trace elements in coal, including assessment of their environmental and health impacts. [Display omitted] •The Trace Elements in Chinese Coals Database Management System (TECC) is constructed.•The distribution of harmful trace elements is analysed.•Harmful trace elements are extremely unevenly distributed in Chinese coalfields.